Pauline Christianity - Ziesler, John A. (Oxford, UK Oxford UP, 1990)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Epistles of Paul -- theology; Paul, the apostle, Saint -- influence; Church history -- primitive and early church, ca. 30-600.